PERAN KELEMBAGAAN DALAM PELAKSANAAN KPS PENYEDIAAN AIR MINUM - Latif Adam; Achsanah Hidayatina (Jurnal Ekonomi dan Pembangunan, 2025)
This paper examines the role of institution in the development of well-run water utility projects using Public Private Partnershif (PPP) scheme. Institutional approach employed in this paper will be focused on the organizational structures and regulations. By using descriptive analysis, this paper conclude that efforts to strengthen organizational structure and regulations are very crucial required to increase the role of institution. It was found that the overlapped function of institutions involved in the implementation of public private partnership projects was caused by unclear mechanism of working relationship among the institutions involved. Efforts to improve organizational structure could be done by building capacity of human resources of the central and local government to upgrade their understanding on the legal aspects, financial and other technical aspects, particularly during the preparation of the PPP projects. In regard to the regulatory issues, the Central and Local Government should have the same view on PPP-Law to provide security and minimize uncertainty for private sector interested invested in the provision of well-run water utility